Study of the Involvement of Pancreastatin in the Physiopathology of Diabetes Mellitus Associated with Nonsecreting Pituitary Adenomas - Prévost, G.; Eas, F.; Duparc, C.; Cauliez, B.; Laquérrière, A.; Fréger, P.; Lefebvre, H.; Kuhn, J. M. (Hormone and Metabolic Research, 2012)
Pancreastatin, derived from chromogranin A, inhibits insulin and stimulates glucagon secretion in rodents. Immunohistochemistry localised pancreastatin in human pancreatic islet cells and gonadotroph pituitary cells. Nonsecreting pituitary adenomas, frequently associated with diabetes mellitus, arise quasi-constantly from gonadotroph cells. We evaluated the possible involvement of pancreastatin in the physiopathology of diabetes mellitus associated with nonsecreting pituitary adenomas. Plasma pancreastatin levels were measured by radioimmunoassay in 5 groups of subjects: 10 patients with nonsecreting pituitary adenomas associated with diabetes mellitus (group I), 10 patients with nonsecreting pituitary adenomas without diabetes (Group II), 10 patients with ACTH or GH-secreting pituitary adenomas and diabetes mellitus (Group III), 10 diabetic patients without pituitary adenomas (Group IV), and 10 healthy controls (Group V). Kidney and liver functions were normal in all of them and no patient was treated with a proton pump inhibitor. All pituitary adenomas were trans-sphenoidally removed. Immunohistochemistry against pancreastatin was performed in 5 patients of each of the 3 groups of pituitary adenomas. Plasma pancreastatin levels were not different between the different groups: 182±46 pg/ml (Group I), 195±57 pg/ml (Group II), 239±42 pg/ml (Group III), 134±31 pg/ml, (Group IV), and 122±29 pg/ml (Group V). In contrast, they were significantly (p<0.05) higher before (391±65 pg/ml) than after trans-sphenoidal surgery (149±18 pg/ml) without post-surgical change in diabetes. An immunostaining against pancreastatin was found in a majority of pituitary adenomas, associated or not with diabetes mellitus. These results argue against a role of pancreastatin in the pathogenesis of diabetes mellitus associated with nonsecreting pituitary adenomas.
Keywords: pancreastatin; diabetes mellitus; nonsecreting pituitary adenomas